Managing biological control services through multi‐trophic trait interactions: review and guidelines for implementation at local and landscape scales. (9th June 2017) - Perović, David J.; Gámez‐Virués, Sagrario; Landis, Douglas A.; Wäckers, Felix; Gurr, Geoff M.; Wratten, Stephen D.; You, Min‐Sheng; Desneux, Nicolas
ABSTRACT: Ecological studies are increasingly moving towards trait‐based approaches, as the evidence mounts that functions, as opposed to taxonomy, drive ecosystem service delivery. Among ecosystem services, biological control has been somewhat overlooked in functional ecological studies. This is surprising given that, over recent decades, much of biological control research has been focused on identifying the multiple characteristics (traits) of species that influence trophic interactions. These traits are especially well developed for interactions between arthropods and flowers – important for biological control, as floral resources can provide natural enemies with nutritional supplements, which can dramatically increase biological control efficiency. Traits that underpin the biological control potential of a community and that drive the response of arthropods to environmental filters, from local to landscape‐level conditions, are also emerging from recent empirical studies. We present an overview of the traits that have been identified to ( i ) drive trophic interactions, especially between plants and biological control agents through determining access to floral resources and enhancing longevity and fecundity of natural enemies, ( ii ) affect the biological control services provided by arthropods, and ( iii ) limit the response of arthropods to environmental filters, ranging from local management practices to landscape‐level simplification. We use this review as a platform to outline opportunities and guidelines for future trait‐based studies focused on the enhancement of biological control services.